ACE inhibitor zofenopril in treatment of myocardial infarction patients: review of SMILE Project trials - Yu. M. Lopatin (Кардиоваскулярная терапия и профилактика)
The results of randomized clinical trials comprising SMILE (The Survival of Myocardial Infarction Long term Evaluation) Project were analyzed. Six-week therapy with an ACE inhibitor zofenopril in acute myocardial infarction (AMI) patients resulted in one-year mortality reduction by 29%. Xofenopril was safe and well-tolerated in AMI patients. Ongoing zofenopril trials are also reviewed.